PERANCANGAN JALUR WISATA BERBASIS CAGAR BUDAYA DI DESA SIRNAJAYA, KECAMATAN SUKAMAKMUR, KABUPATEN BOGOR - Razak, Januarani; Hendarmawan; Irawati, Ira (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2022)
Sirnajaya Village is one of the nature-based tourist destinations in Bogor Regency. Its potential as a natural tourist destination has not been matched by maximizing the supporting components of tourism activities, one of which is professionally managed tourism flows. This village has various historical heritages typical of Sundanese culture that should be protected and preserved, one of which is the Grave of Eyang Surya Kencana. The absence of clear guidelines and systems on tourism management in this village can threaten the sustainability of its historical value. Based on this, this study aims to design a cultural-based tourism route in Sirnajaya Village. The research method used consists of data collection methods and data analysis methods. Research data collection was carried out by field observations, interviews with community leaders, and secondary data collection through relevant literature. Data such as the condition of tourist destinations and historical stories of the formation of Sirnajaya Village are then processed through qualitative descriptive analysis methods, SWOT analysis (Strenghts, Weaknesses, Opportunities, Threats) to produce recommendations, as well as Google Earth spatial analysis to determine tourist routes based on their potential. The results of the research are in the form of directions for the development of a tourist route that stretches from Raden Wargajaya’s Tomb at the village entrance to the grave of Eyang Surya Kencana in the Situ Rawa Gede area. This tourist route recommendation is expected to help the development and conservation of cultural heritage in Sirnajaya Village through tourism activities.